Indonesian Legal Politics of Islamic Boarding School Curriculum Regulation - Faiqatul Husna; Nur Rohim Yunus; Andri Gunawan (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Islamic boarding school education acts as a service industry by meeting quality standards. An institution can be called qualified if it meets the specifications that have been set through existing regulations. Regarding the use of the curriculum, Islamic boarding schools are autonomously entitled to regulate and choose the curriculum according to the needs of the local community. However, it remains within the scope of the law that regulates it. The regulation is in the form of the Law on Islamic Boarding Schools by giving recognition to several curricula. This study uses a qualitative research method with a literature approach. The results of the study stated that there were several conditions that resulted in changes to the educational curriculum, including changes in organizational structure, monitoring mechanisms of the expected results, and the creation of power to make changes or replacement of the curriculum.Keywords: Islamic Boarding School Curriculum; Legal Policy; Islamic boarding school Abstrak:Pendidikan pondok pesantren berperan sebagai industri jasa dengan memenuhi standar kualitas. Lembaga dapat disebut berkualitas apabila memenuhi spesifikasi yang telah ditetapkan melalui regulasi yang ada. Terkait penggunaan kurikulum, pesantren secara otonomi berhak mengatur dan memilih kurikulum dengan menyesuaikan kebutuhan masyarakat setempat. Namun, tetap dalam lingkup undang-undang yang mengatur. Pengaturannya dalam bentuk Undang-Undang tentang Pesantren dengan memberikan pengakuan pada beberapa kurikulum. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan literatur. Hasil penelitian menyatakan bahwa terdapat beberapa kondisi yang mengakibatkan perubahan kurikulum pendidikan, diantaranya adalah perubahan struktur organisasi, mekanisme monitoring dari hasil yang diharapkan, dan terciptanya kekuatan untuk melakukan perubahan atau penggantian kurikulum.  Kata Kunci: Kurikulum Pesantren; Kebijakan Hukum; Pondok Pesantren